Agroforestry, principles and practices - Dwivedi, A. P., 1945- (New Delhi : Oxford & IBH Pub. Co., 1992)
With reference to India.
Includes bibliographical references (p. [321]-335) and index.
Keywords: Agroforestry; Agroforestry -- India